2006
DOI: 10.1152/ajpendo.00244.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of differing antecedent hypoglycemia on counterregulatory responses to exercise in type 1 diabetes

Abstract: Hypoglycemia frequently occurs during or after exercise in intensively treated patients with type 1 diabetes mellitus (T1DM), but the underlying mechanisms are not clear. In both diabetic and nondiabetic subjects, moderate hypoglycemia blunts counterregulatory responses to subsequent exercise, but it is unknown whether milder levels of hypoglycemia can exert similar effects in a dose-dependent fashion. This study was designed to test the hypothesis that prior hypoglycemia of differing depths induces acute coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 45 publications
2
45
1
4
Order By: Relevance
“…The finding that antecedent hypoglycaemia has little or no effect on the glucoregulatory response to sprinting was unexpected considering the findings of Galassetti and colleagues [21,22], who reported that antecedent hypoglycaemia reduces the glucoregulatory response to moderate-intensity exercise in individuals with type 1 diabetes. In particular, they showed that although antecedent hypoglycaemia has no effect on growth hormone responses to moderate-intensity exercise it results in diminished adrenaline, noradrenaline, glucagon and cortisol responses [21,22].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The finding that antecedent hypoglycaemia has little or no effect on the glucoregulatory response to sprinting was unexpected considering the findings of Galassetti and colleagues [21,22], who reported that antecedent hypoglycaemia reduces the glucoregulatory response to moderate-intensity exercise in individuals with type 1 diabetes. In particular, they showed that although antecedent hypoglycaemia has no effect on growth hormone responses to moderate-intensity exercise it results in diminished adrenaline, noradrenaline, glucagon and cortisol responses [21,22].…”
Section: Discussionmentioning
confidence: 93%
“…Since an episode of hypoglycaemia can reduce the glucoregulatory response to a subsequent bout of moderate-intensity exercise [21,22], the purpose of this study was to investigate the possibility that antecedent hypoglycaemia impairs both the glucoregulatory and glycaemia-increasing responses to a 10 s sprint. This study shows that morning hypoglycaemia does not attenuate the glycaemia-increasing effect of a 10 s sprint performed in the afternoon and has little or no effect on the glucoregulatory response to this type of exercise in young adults with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations